The Issue Of Secular State And Religious Policy In The Soviet Period (Zien Journal of Social Sciences and Humanities, 2026)
This article analyzes the formation of the concept of a secular state and the main stages of religious policy in the Soviet era. The contradiction between the proclamation of legal secularism and the primacy of ideological atheism in practice is revealed. Also, the policy of "scientific atheism", the pragmatic approach during the Second World War, and the differences between the Soviet model and modern secular state concepts are scientifically highlighted. The research is conducted based on the method of historical and political analysis